PELATIHAN PEMBUATAN LAPORAN KEUANGAN BAGI UMKM KALAPA INDUNG - Silviana; Rita Yuniarti; Achmad Fadjar; Nuryaman; Aswina Baharuddin; Vita Anggrayni (Divisi Pengabdian dan Pemberdayaan Masyarakat (DP2M) UNIKOM, 2026)
Small and Medium Enterprises (SMEs) face challenges in determining the profits from their business activities. SMEs under the coordination of Kalapa Indung (West Java Women School) face the same issues. The separation of household accounting from business accounting has not been made, making it difficult to determine business profits. The aim of the community service activity conducted by the Faculty of Postgraduate School, MAKSI-UTAMA program, is to assist SME actors in understanding simple accounting, understanding accounts, elements of financial statements, and bookkeeping. The community service program involves MAKSI students to assist in the preparation of simple financial statements for SMEs. Preparations for the community service program have been made through Focus Group Discussions (FGD) among cluster members and the committee, also involving the coordinator of SMEs Kalapa Indung as a partner. The community service activities have been carried out in person, with presentations, discussions, and mentoring that engage the enthusiasm of the participants. The results of the PKM activities indicate that in resolving case studies related to bookkeeping, MSME actors are not capable of preparing financial statements (balance sheets and income statements). Thus, it is hoped that the knowledge acquired by MSME actors can be implemented in MSME business activities, enabling them to manage their finances more effectively.